1996
DOI: 10.1007/bf00185296
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of the data determined by scanning laser polarimetry

Abstract: The instrument is clinically useful only if used by the same observer. If measurements are performed by different observers the ratios of the measurements must be used. Further development in the apparatus is needed to improve interobserver reproducibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Several investigations have reported that the reproducibility of measurements made by the NFA is generally better than that made by OCT [20, 21, 22, 23, 24, 25, 26, 27]. The results of this study are almost consistent with those of previous reports.…”
Section: Discussionsupporting
confidence: 83%
“…Several investigations have reported that the reproducibility of measurements made by the NFA is generally better than that made by OCT [20, 21, 22, 23, 24, 25, 26, 27]. The results of this study are almost consistent with those of previous reports.…”
Section: Discussionsupporting
confidence: 83%
“…Sessions took place at a 1-week interval and were performed by the same operator. Previous papers evaluated reproducibility of SLP measurements with older versions of the Nerve Fiber Analyzer (I, II, and GDx with fixed corneal compensation) [17,18,19,20,21,22,23,24,25,26]. Overall results were fair to good.…”
Section: Discussionmentioning
confidence: 90%
“…Another feature that any reliable diagnostic instrument must possess is high reproducibility of measurements, mainly for disease follow-up. Reproducibility of measurements with older versions of GDx have previously been assessed in detail [17,18,19,20,21,22,23,24,25,26]. More recently a few papers evaluated GDx-VCC interdevice [27], intraoperator [28] or intraobserver reproducibility [29].…”
Section: Introductionmentioning
confidence: 99%
“…The NFA used for our study has already shown good reproducibility [4, 9, 10], above all in its second version [6]. Nevertheless, we have to consider that there is the risk, due to the variable interindividual number of fibers at birth, to underestimate the RNFL thickness of subjects with a thick baseline value, as well as to overestimate the thinning of RNFL in subjects with a thin baseline value of RNFL.…”
Section: Discussionmentioning
confidence: 99%
“…Its specificity has been evaluated good even if certain interobserver variability has been described. Some technical changes to the second version of this machine have improved the reproducibility of its measurements [6, 9, 10]. …”
Section: Introductionmentioning
confidence: 99%